Operation‐based approach for documenting software architecture knowledge. Issue 4 (25th May 2016) - Roldán, María Luciana; Gonnet, Silvio; Leone, Horacio
Abstract: Documenting architectural knowledge is a tedious and time‐consuming task from the knowledge producer's point of view. As a consequence, design decisions, the underlying rationale, and the resulting designs are poorly documented. We propose to alleviate this problem by introducing an operation‐based model for documenting software architecture design processes, which makes possible to capture architectural knowledge in a non‐intrusive way as the design process takes place. By means of a flexible model that makes possible the definition and execution of different level's operations, such as operations that enclose patterns and tactics semantics, we ensure codification of general architectural knowledge and enable its recovering to use it in several design projects. From the knowledge consumers' point of view, the model provides tracing capabilities and useful mechanisms for architectural knowledge recovering.